2014
DOI: 10.1161/circulationaha.113.004420
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in Relation to the Effects of Ticagrelor in Comparison With Clopidogrel in Non–ST-Elevation Acute Coronary Syndrome Patients Managed With or Without In-Hospital Revascularization

Abstract: Background-Risk stratification and the use of specific biomarkers have been proposed for tailoring treatment in patients with non-ST-elevation acute coronary syndrome (NSTE-ACS). We investigated the prognostic importance of highsensitivity troponin T (hs-TnT), N-terminal pro-brain natriuretic peptide (NT-proBNP), and growth differentiation factor-15 (GDF-15) in relation to randomized treatment (ticagrelor versus clopidogrel) and management strategy (with or without revascularization) in the NSTE-ACS subgroup o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 35 publications
2
74
0
4
Order By: Relevance
“…GDF‐15 was measured with a precommercial assay (Roche Diagnostics) using a monoclonal mouse antibody for capture and a monoclonal mouse antibody fragment for detection in a sandwich assay format. The results of these analyses in relation to outcomes and effects of study treatment have previously been reported 8, 9, 10…”
Section: Methodsmentioning
confidence: 90%
See 4 more Smart Citations
“…GDF‐15 was measured with a precommercial assay (Roche Diagnostics) using a monoclonal mouse antibody for capture and a monoclonal mouse antibody fragment for detection in a sandwich assay format. The results of these analyses in relation to outcomes and effects of study treatment have previously been reported 8, 9, 10…”
Section: Methodsmentioning
confidence: 90%
“…Several biomarkers, on admission for ACS, provide clinically important information on risk for cardiovascular morbidity and mortality, including NT‐proBNP (myocardial dysfunction),9, 10 cardiac troponins (myocardial necrosis),29 and cystatin C (kidney function) 7, 11. Circulating osteoprotegerin has been reported to be associated with cardiovascular outcomes, including mortality, MI, and incident heart failure, in several ACS cohorts 16, 17, 18, 19.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations